Penghentian Akad Gadai dalam Perspektif Hukum Ekonomi Syariah - Mulyono, Edi; Darussalam, Hidayat; Nikman Naser, Muhammad (Dalwa Islamic Economic Studies: Jurnal Ekonomi Syariah, 2023)
This study aims to find out how to terminate a pawn contract and review sharia economic law on terminating a pawn contract in Abung Barat District. To discuss these problems, researchers used descriptive qualitative research methods, with data collection techniques through: observation, interviews and documentation. Based on the results of the research that has been done, it can be concluded that the settlement in terminating the pawn agreement is resolved in several ways, namely: resolved in a familial manner, there is a settlement of transferring the pawn recipient, and there is also a return to the initial agreement; In a review of sharia economic law on termination of pawn contracts in Abung Barat District, North Lampung, that the implementation of pawning in West Abung District is in accordance with sharia economic law, this is because the implementation of the pawn system is appropriate or has fulfilled the legal basis for terminating a contract. , where what happened in the field the pawnbroker stopped by deliberation to reach a consensus.